Systematic review and meta‐analysis on the association between theory of mind and alcohol problems in non‐clinical samples. (26th September 2022) - Kumar, Lakshmi; Skrzynski, Carillon J.; Creswell, Kasey G.
Abstract: Background: Deficits in theory of mind (ToM) found in individuals with alcohol use disorder (AUD) are often thought to result from prolonged heavy alcohol use. However, links between deficits in ToM and greater alcohol problems are often also present in non‐clinical samples (e.g., adolescents and young adults) who may not have a similar long‐lasting history of alcohol consumption as individuals with AUD. The current study is the first to systematically review and meta‐analyze results from studies examining associations between lower ToM and greater alcohol problems in non‐clinical samples. Evidence of reliable associations in these non‐clinical samples would support the idea that deficits in ToM might also precede the emergence of AUD. Methods: PsycINFO, PubMed, and Google Scholar were searched according to our preregistered International Prospective Register of Systematic Reviews (PROSPERO) protocol (CRD42021225392) and following the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) methodology. We systematically reviewed sample characteristics and ToM measures in identified articles. We then meta‐analyzed the findings of association between ToM and alcohol problems in non‐clinical samples using random effects models. Results: Nearly all studies used a measure of ToM that assessed the ability to infer the mental states of others based on eye region cues. Meta‐analytic results demonstrated that lower ToM was associated with more alcohol problems ( r  = −0.16, k  = 6, CI = [−0.26, −0.04], p  < 0.01, Q  = 15.55, I 2  = 67.85), and there was significant heterogeneity across studies. Gender ( ß  = 0.0003, CI = [−0.006, 0.007], z = 0.09, p  = 0.93), age ( ß  = −0.008, CI = [−0.03, 0.01], z = −0.82, p  = 0.42), and study quality ( ß  = −0.10, CI = [−0.35, 0.15], z = −0.82, p  = 0.41) did not explain the heterogeneity. Conclusion: In non‐clinical samples, lower ToM is associated with more alcohol problems, indicative of a small effect size. Future longitudinal studies are needed to explore whether socio‐cognitive deficits may also serve as a risk factor for alcohol misuse. Abstract : This study is the first to systematically review and meta‐analyze results from studies examining associations between theory of mind (ToM) and alcohol problems in non‐clinical samples. Most studies used a measure of ToM that assessed the ability to infer the mental states of others based on eye region cues. Meta‐analytic results demonstrated that lower ToM was reliably associated with more alcohol problems in non‐clinical samples.